Reassessing standards of vascular access device care: a follow-up audit. (25th April 2019) - McGuire, Rose; Norman, Ellen; Hayden, Iain
Abstract : This article reports on the findings of a repeat audit of vascular access devices (VADs) in a district general hospital undertaken 4 years after a previous audit. The first demonstrated poor standards of care and low compliance with evidence-based guidelines, indicating that a change in practice was necessary. A strategy of training, education and standardisation for intravenous devices was introduced, with the goal of transforming practice to raise standards and improve compliance. The findings of the follow-up audit show that the strategy has been successful in raising standards of care and reducing infections.